2015
DOI: 10.1165/rcmb.2014-0179oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Alveolar Procoagulant Activity and Permeability in Direct Acute Lung Injury by Lung Epithelial Tissue Factor

Abstract: Tissue factor (TF) initiates the extrinsic coagulation cascade in response to tissue injury, leading to local fibrin deposition. Low levels of TF in mice are associated with increased severity of acute lung injury (ALI) after intratracheal LPS administration. However, the cellular sources of the TF required for protection from LPS-induced ALI remain unknown. In the current study, transgenic mice with cell-specific deletions of TF in the lung epithelium or myeloid cells were treated with intratracheal LPS to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 48 publications
4
50
0
1
Order By: Relevance
“…In contrast, other studies using animal models of indirect ALI have suggested that TF deficiency or systemic TF inhibition reduced tissue injury12131415. We recently identified that TF expressed on the lung epithelium was the predominant source of TF in the lung during direct LPS-induced ALI16, with no significant contribution of TF from myeloid cells in this model. This finding was in contrast to prior data showing that TF expressed on cells in the circulation was critical for the systemic response to LPS in a model of endotoxemia17.…”
mentioning
confidence: 64%
“…In contrast, other studies using animal models of indirect ALI have suggested that TF deficiency or systemic TF inhibition reduced tissue injury12131415. We recently identified that TF expressed on the lung epithelium was the predominant source of TF in the lung during direct LPS-induced ALI16, with no significant contribution of TF from myeloid cells in this model. This finding was in contrast to prior data showing that TF expressed on cells in the circulation was critical for the systemic response to LPS in a model of endotoxemia17.…”
mentioning
confidence: 64%
“…19,60,61 In fact, the difference in potency between these 2 agents may be more significant than their relative concentrations would suggest, as only a fraction of hTM/R6.5 molecules would have bound to the cell membrane. While ICAM-1 targeting of hTM/R6.5 was limited to hematopoietic and ECs in these studies, other cell types, such as epithelium, express ICAM-1, and may be both an important source of TF 24 and a valuable target of this approach. 62 There are several reasons why binding of TM to cell membranes may enhance its antithrombotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to discern the contribution of endothelial TF from other sources such as hematopoietic cells, epithelium, fibroblasts, pericytes, and smooth muscle. [22][23][24] While ECs express TF under inflammatory stimuli in vitro, studies have failed to (E) hTM/R6.5 binds strongly to TNF-a-stimulated HUVEC but only minimally to nonstimulated ECs. Cell-based enzyme-linked immunosorbent assays were performed on live cells as previously described 19 using anti-FLAG-HRP to probe for cell-bound fusion protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure 3C, treatment with BIO-11006 provoked a significant decrease in mRNA expression of these cytokines in the lung, suggesting effects at the message level. MARCKS also has been shown to be involved in activation of NF-kB in different cells (19)(20)(21), perhaps through a protein kinase C d-related mechanism (22), and it is known that KC and TNF-a-contain NF-kB-binding sites in their promoter regions, so a logical next step was to look at whether or not BIO-11006 could affect NF-kB. Using phosphorylation of the p65 subunit of NF-kB in lung cytoplasmic extracts as an indicator of NF-kB activation, inhalation of BIO-11006 at any of the time points in this study inhibited LPS-induced NF-kB activation (Figure 4).…”
Section: Actin-binding Function Of Marcks (4)mentioning
confidence: 99%